Fasting glucose and its association with 20-year all-cause and cause-specific mortality in Chinese general population - Long Zhou; Jin-Zhuang Mai; Ying Li; Yong Wu; Min Guo; Xiang-Min Gao; Yang-Feng Wu; Lian-Cheng Zhao; Xiao-Qing Liu (Chronic Diseases and Translational Medicine, 2019)
Objective: The aim of this study was to explore the relationship between fasting glucose levels and all-cause and cause-specific mortality in Chinese population. Methods: The role of fasting blood glucose levels as a predictor of all-cause and cause-specific mortality was estimated in 9930 participants from four Chinese general populations with a 20-year follow-up. Multivariate Cox proportional hazard models were used to identify the relationship between fasting glucose and mortality. Results: There were 1471 deaths after a median follow-up of 20.2 years (a total of 187,374 person-years), including 310 cardiovascular deaths, 581 cancer deaths, and 580 other-cause deaths. After adjustment for age, sex, urban or rural, northern or southern of China, types of work, education level, physical exercise, smoking status, drinking status, body mass index, systolic blood pressure, and serum total cholesterol at baseline, the hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause mortality in the fasting blood glucose categories of <60, 60–69, 70–79, 90–99, 100–109, 110–125, and ≥126 mg/dl were 1.38 (1.04–1.84), 1.20 (1.01–1.43), 1.18 (1.03–1.36), 1.18 (0.99–1.41), 1.48 (1.16–1.88), 1.17 (0.84–1.62), and 2.23 (1.72–2.90), respectively, in contrast to the reference group (80–89 mg/dl). The HRs and 95% CIs for cardiovascular disease mortality in these groups were 2.58 (1.44–4.61), 1.41 (0.95–2.10), 1.56 (1.15–2.11), 1.29 (0.88–1.89), 1.36 (0.78–2.37), 1.05 (0.52–2.11), and 2.73 (1.64–4.56), respectively. Conclusions: Both low and high fasting glucose were significantly associated with increased risk of all-cause and cardiovascular mortality in Chinese general population. Keywords: Fasting blood glucose, Mortality, Cardiovascular disease, Cohort study